Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.608
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Time Pressure in Scrum Projects: Insights from a Qualitative Study

Abstract: Time pressure represents one of the most critical factors associated with software development project failure. However, its role in previous research is limited to traditional development approaches and is also inconclusive, suggesting both negative and positive effects, while others argue for dependence on the level of time pressure. In the context of agile software development projects, particularly Scrum, we seek to analyze the role of time pressure in software development projects and aim to develop a bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, the participants attributed limited time availability to Agile practices. A study by Linß et al found ten antecedents to, and five consequences of time pressure, by analysing time pressure in software projects that apply Scrum [37]. It is evidence that time pressure is intrinsic to the agile development method -scrum.…”
Section: Classification Of Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the participants attributed limited time availability to Agile practices. A study by Linß et al found ten antecedents to, and five consequences of time pressure, by analysing time pressure in software projects that apply Scrum [37]. It is evidence that time pressure is intrinsic to the agile development method -scrum.…”
Section: Classification Of Antecedentsmentioning
confidence: 99%
“…According to our results, ambiguous and incomplete requirements promote a disconfirmatory behaviour, however, under time pressure this leads to a confirmatory behaviour manifestation. More studies are needed on how to improve the requirement specifications that may deteriorate software quality especially in the context of Agile that also constraints time [37]. Yet, the manifestation of confirmation bias in the case of complete requirements is not detrimental for software quality because a tester is then validating all the specified required and not required behaviours of the SUT [3].…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…There are multiple reasons that create (negative) time pressure in software projects. For example, budget constraints, bottlenecks due to functional dependencies, inadequate time estimations, change of requirements during sprints (agile development method), dependencies on external suppliers, and technical uncertainties are the usual grounds for time pressure [42], [43], [44]. Another factor that constrains the development schedule is the competition in the global market [43].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled experiments in the lab have investigated the impact of sleep deprivation [17], emotional arousal induced by time pressure [38] and emotional states of dominance and valence [18]. Quantitative [46] and qualitative studies [34] have showed the impact of time pressure on the field. Studies on mining software repositories have made several recent attempts to build tools and reason about the emotional states of software developers by utilizing sentiment analysis [23,24,33,37,47].…”
Section: Introductionmentioning
confidence: 99%